Midwifery curricula inclusion of sexual and reproductive health in crisis settings in the Democratic Republic of Congo. (August 2021) - Lordfred, Achu; Tran, Nguyen Toan; Nzee, Alexis; Kabeya, Ambrocckha; Mukumpuri, Guy; Eke, Henriette; Kini, Brigitte; Greer, Alison; Hounton, Sennen
Abstract: Aim: This discussion paper aims to argue for the inclusion of the Minimum Initial Service Package (MISP) for sexual and reproductive health in crisis settings in all midwifery curricula. Background: The Democratic Republic of Congo continues to experience long-standing humanitarian crises that have affected the population's health, especially in relation to sexual violence and other sexual and reproductive health issues. The MISP was established in 1996 to meet the most vital sexual and reproductive health needs of crisis-affected populations and has become an international minimum standard in humanitarian response. Design: Case study. Methods: This paper is a case presentation describing the process and lessons learned related to the introduction of the MISP into the first- and third-year pre-service midwifery curricula at multiple midwifery education facilities in the Democratic Republic of Congo. Results: Six main lessons were identified during the initial implementation phases of the revised midwifery curricula: seizing the opportunity to influence long-term change, engaging teamwork, addressing instructors' concerns, mobilizing resources for curriculum implementation, assessing school infrastructure readiness during field visits, and meeting immediate humanitarian needs with in-service training. The lessons learned may assist other nations experiencing humanitarian crises with the implementation of the MISP. Conclusions: This pre-service training strategy holds promise for both a sustainable and prompt solution to bridge the gap in competent human resources to deliver quality sexual and reproductive health services in humanitarian settings.